Effects of multiple-intensity SSIT pairing patterns on explosive power and skill performance in female basketball players - Cao, Junsheng; Lin, Jinyang; Wang, Xiangying; Wang, Yulong (Frontiers in Physiology, 2025)
BackgroundExplosive power and skill performance are critical components of basketball success, particularly in female athletes whose neuromuscular and physiological responses may differ from males. While Short Sprint Interval Training (SSIT) is recognized for improving aerobic and anaerobic capacity, its effect on explosive performance remains underexplored, especially across varied intensity pairings.MethodsA randomized controlled trial was conducted involving 36 female collegiate basketball players assigned to high-intensity (HI-SSIT), moderate-intensity (MI-SSIT), or multiple-intensity (MUL-SSIT) SSIT protocols over 8 weeks. Pre- and post-intervention assessments included vertical jump (CMJ, approach jump), sprint (10 m, 20 m), agility (Modified T-test, defensive slide), repeated sprint ability (RSA), intermittent endurance (YYIR1), and physiological markers (heart rate, blood lactate).ResultsMUL-SSIT showed “possibly” beneficial effects on jump height decrement, sprint performance, and heart rate recovery compared to other protocols. While all groups improved in RSA and endurance capacity (p < 0.001), MUL-SSIT had the greatest gains in 10 m sprint and fatigue resistance. No significant improvements were observed in CMJ or agility across groups. Heart rate recovery improved in all protocols, with MUL-SSIT showing the most favorable outcomes.ConclusionMultiple-intensity SSIT protocols are effective in enhancing fatigue resistance, sprint capacity, and certain aspects of explosive performance in female basketball players. These findings support the inclusion of varied-intensity SSIT formats in basketball conditioning programs to better address sport-specific demands.